Self-healable and 4D printable hydrogel for stretchable electronics - Li, Huijun (2024)
Materials with high stretchability and conductivity are used to fabricate stretchable electronics. Self-healing capability and four-dimensional (4D) printability are becoming increasingly important for these materials to facilitate their recovery from damage and endow them with stimuli-response properties. However, it remains challenging to design a single material that combines these four strengths. Here, a dually crosslinked hydrogel is developed by combining a covalently crosslinked acrylic acid (AAC) network and Fe3+ ions through dynamic and reversible ionically crosslinked coordination. The remarkable electrical sensitivity (a gauge factor of 3.93 under a strain of 1500%), superior stretchability (a fracture strain up to 1700%), self-healing ability (a healing efficiency of 88% and 97% for the mechanical and electrical properties, respectively), and 4D printability of the hydrogel are demonstrated by constructing a strain sensor, a two-dimensional touch panel, and shape-morphing structures with water-responsive behavior. The hydrogel demonstrates vast potential for applications in stretchable electronics.